Integrating intra- and interpersonal perspectives on chronic low back pain: the role of emotion regulation and attachment insecurity - Yixin Yang; Dominik Mischkowski (Frontiers in Psychology, 2024)
ObjectiveChronic low back pain (CLBP) is burdensome and interferes with psychological and physical functioning of those affected. Past research has examined interpersonal (e.g., attachment insecurity) or intrapersonal factors (e.g., emotion regulation [ER]) involved in chronic pain. However, to enhance our understanding of CLBP’s biopsychosocial underpinnings, more empirical integration of both intra- and interpersonal factors involved in CLBP is needed. Thus, our study examined the independent and joint associations of insecure attachment dimensions and ER strategies with CLBP severity and interference.MethodsWe recruited 242 US adults with CLBP through Prolific Academic, an online participant pool. Participants from Prolific Academic were eligible for the study if they were at least 18 years of age, resided in the US, reported CLBP at least half the days over the past 6 months (>3 months), and used prescribed pain medication for their CLBP. Data collection was between November 2021 and February 2022. Eligible participants filled out a Qualtrics survey which consisted of measures assessing insecure attachment dimensions, ER strategies, as well as demographical information. Outcome variables in the present study were CLBP severity and interference. We ran multiple linear regression models to examine the associations between ER strategies and insecure attachment dimensions as predictors, and CLBP severity or interference as predicted variables, after controlling for sex as a covariate; we also conducted moderation analyses to investigate the interactions between ER strategies and insecure attachment dimensions when testing associations with CLBP severity or interference.ResultsOur results indicated that, after controlling for ER strategies, anxious attachment was positively associated with CLBP interference but not pain severity (CI: 0.101 to 0.569; CI: −0.149 to 0.186); avoidant attachment was not associated with CLBP interference or severity (CI: −0.047 to 0.511; CI: −0.143 to 0.256). After adjusting for anxious and avoidant attachment, emotional expression and expressive suppression were positively associated with CLBP severity (CI: 0.037 to 0.328; CI: 0.028 to 0.421) but not interference (CI: −0.003 to 0.403; CI: −0.406 to 0.143). Furthermore, emotional expression was associated with CLBP severity and interference at low and medium levels of avoidant attachment (CI: 0.165 to 0.682; CI: 0.098 to 0.455); expressive suppression and cognitive reappraisal did not interact with attachment dimensions when examining CLBP severity or interference (CIs: LLs ≤ −0.291 to ULs ≥ 0.030).ConclusionOur study shows that anxious attachment may be an interpersonal risk factor related to CLBP, above and beyond intrapersonal ERs, as anxious attachment was associated with higher levels of pain interference. Furthermore, emotional expression was associated with increased CLBP severity and interference, particularly among individuals at low and medium levels of avoidant attachment. Existing studies on chronic pain have mostly focused on examining intrapersonal or interpersonal correlates in isolation. The present study extends our understanding of CLBP by considering the role of interpersonal factors (i.e., insecure attachment dimensions), in combination with intrapersonal ER strategies. Given the correlational nature of the present study, longitudinal studies are needed to establish causality between psychosocial correlates and CLBP symptoms. Ultimately, we hope our integrated approach will facilitate the development of treatments and interventions tailored to address patients’ attachment-related needs, enhancing the management and maintenance of CLBP among patients.